11 Years of Rayleigh Lidar Observations of Gravity Wave Activity Above the Southern Tip of South America. Issue 2 (17th January 2019) - Llamedo, P.; Salvador, J.; de la Torre, A.; Quiroga, J.; Alexander, P.; Hierro, R.; Schmidt, T.; Pazmiño, A.; Quel, E.
Abstract: Gravity wave (GW) activity is analyzed using temperature ( T ) data retrieved from a Rayleigh light detection and ranging (lidar) at Río Gallegos, Argentina (51.6°S, 69.3°W). GW characteristics are derived from 302 nights of observations providing more than 1, 018 hr of high‐resolution lidar data between 20‐ and 56‐km height from August 2005 to December 2015. T measurements are performed by a Differential Absorption Lidar instrument. This lidar was the southernmost outside Antarctica until the end of 2017. Río Gallegos is an exceptional place to observe large amplitude GW. Every lidar measurement is classified according to its relative position to the polar vortex. The lidar measurements are compared with collocated Sounding of the Atmosphere using Broadband Emission Radiometry and Global Positioning System‐Radio Occultation data. The different instruments show different windows of the GW spectrum, providing complementary observations. In general, the geometric mean of the specific GW potential energy ( PE ) is larger during winter and spring than during summer and autumn. The largest geometric mean of PE is found inside the vortex and decreases monotonically at its edge, outside it and when there is no vortex. The same behavior is observed with satellite data. On average, it can be seen that lidar observations provide larger PE values than limb sounding measurements. From a Morlet continuous wavelet transform analysis, three distinct modes are captured from Sounding of the Atmosphere using Broadband Emission Radiometry and from Global Positioning System‐Radio Occultation data at the upper and lower stratosphere, respectively. In particular, a systematic 3.5‐ to 4‐year oscillation, possibly related to El Niño–Southern Oscillation is observed. Key Points: The GW activity derived from 302 nights of lidar measurements above a subpolar region and from collocated satellite measurements is evaluated The GW specific potential energy from lidar and satellite measurements is larger inside the polar vortex than outside it or at its edge The specific potential energy is larger during winter and spring